Konstruksi Realitas Media: Analisis Framing Pemberitaan Jokowi dalam Kasus OCCRP - Shidik, Ma’arif Fadhilah; Florina, Ike Desi; Permadi, Didi (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This research analyzes how online media, especially Tempo.co, analyzes and influences people's views on the issue of Jokowi's inclusion in the Organized Crime and Corruption Reporting Project (OCCRP)'s 2024 most corrupt figure nomination. Using Robert N Entman's framing analysis, this research highlights how Tempo.co chooses and emphasizes certain aspects to shape the wider community's perception. The results showed that Tempo.co emphasized the ineffectiveness of anti-corruption policies during Jokowi's administration and its impact on the political image that had been built. It was also found that the media framing showed a strong reaction from Jokowi's supporters, which led to threats against anti-corruption activists, which shows the complexity of political dynamics in Indonesia. This research makes it clear that the media significantly influences public opinion on controversial political issues.